Ferro, Jorge (ed.). Pedro López de Ayala, Crónica del rey don Juan Primero. Buenos Aires, SECRIT, 2009, XXX+402 pp. - Sarracino, Pablo E. (2010)
Fil: Sarracino, Pablo E. Universidad de Buenos Aires; Argentina